Tasfir Peshat terhafap Perkawinan Campur dari Anak-anak Allah di dalam Kejadian 6:1-4 - Jujung Rilman Tambunan; Kalis Stevanus (PASCA : Jurnal Teologi dan Pendidikan Agama Kristen, 2023)
This article seeks to read the meaning of mixed marriage for God's children in the text of Genesis 6:1-4 through the peshat interpretation. This interpretation approach is one of the traditional Jewish hermeneutical methods. It is hoped that with this approach, a more profound explanation can be obtained regarding the context of marriage at that time so that it also triggers and causes "God's regrets." The offspring from this marriage created a gene mixture between the sons of God and the daughters of men. The result is that the children of God referred to in the text are pious descendants of Seth, one of Noah's sons, and married to an ungodly woman from Cain's lineage. Suppose a marriage is only determined based on one's desires and does not fulfill the elements of God's will. In that case, the person will inevitably walk in disobedience to God and continue to live in his condition as a sinful human being.